Surface Modification of Nanocrystalline Cellulose toward a Tunable Optical Polarizer. Issue 10 (2016) - Bolduc, Martin; Poirier, Michel; Chauve, Gregory; Oulachgar, Hassane; Tiwald, Tom; Laperle, Pierre; Gay, David; Beaupre, Patrick; Methot, Myriam; Leclerc, Melanie; Deshaies, Sebastien; Briand, Martin; et al.
ABSTRACT: Nanocrystalline cellulose (NCC) solid films obtained from evaporated aqueous heterogeneous mixtures retain the self-assembled chiral nematic order formed in the suspension. These semi-translucent films are iridescent and reflect or transmit circularly polarized visible light (400-700nm) due to the chiral properties of the self-assembled nanostructure. This effect occurs at different wavelengths depending on the pitch of the helical structure. In this paper, NCC films have been fabricated from different recipes to produce various helix pitches. The corresponding red-shift in the optical wavelength has been obtained by means of Spectrophotometry measurements. Preliminary experiments have been performed to investigate optical polarization effects as function of angles of incidence using ellipsometry. Finally, laser micromachining results on NCC films may suggest feasibility for integration as tunable light polarizer components.